Penyuluhan Antibiotik untuk Meningkatkan Pengetahuan Masyarakat Dukuh Kwageyan Desa Bulusan Kecamatan Karangdowo Kabupaten Klaten Jawa Tengah - Nafisah , Umi; Putri, Vania Santika; Sukmawati, Nina; Ayu, Salsabila Dyah (Pakis Journal Institute, 2025)
Unwise use of antibiotics is a global health problem that can increase the risk of bacterial resistance. People often use antibiotics without a doctor's prescription, do not finish the medication as recommended, or use them for conditions that do not require antibiotics. Counseling is an educational effort to increase public understanding regarding the rational use of antibiotics. This community service activity aims to provide education about antibiotics and resistance to the people of Dukuh Kwageyan, Bulusan Village, Karangdowo District, Klaten Regency, Central Java. The method used is counseling using presentation media and leaflets, as well as evaluation through pre-test and post-test to measure the increase in participants' knowledge. A total of 68 elderly Posyandu participants took part in this activity. The pre-test results showed that the level of public knowledge was 56.07% (fair category), which increased to 85.24% (good category) after the post-test. This increase shows that the education method is effective in increasing public awareness and understanding regarding the appropriate use of antibiotics. Continuous education is needed to minimize the risk of antibiotic resistance in the community.